Seismic design and evaluation of moment resisting frames using elastomeric dampers - Basagiannis, C (2018)
This study evaluates the characteristics of elastomeric dampers, and assesses their eectiveness in mitigating the eects of dynamic loading. As part of this evaluation a series of characterization tests were carried out in order to extract the main mechanical properties of the elastomer material in a range of strain amplitudes, loading frequencies, and ambient temperatures, since it has been proved that elastomeric materials depend on these parameters. It was found that strain amplitude was the most dominant factor not only regarding the values of their mechanical properties (shear storage modulus, and loss factor) but also with regard to the shape of the hysteresis loops. At the same time frequency was shown to have only a minor eect on their behaviour. Based on the Generalised Maxwell Model, a new hysteretic model was developed and proposed in this thesis which is able to capture the behaviour of the material. As part of this model an equation was derived which describes the force-displacement relationship of the Generalised Maxwell Model for N Maxwell elements in time domain, and formed the basis for the proposed model. The seismic performance of a 10 storey steel moment resisting frame was evaluated, and the eect of the dampers on the frame's performance was examined. The dampers were designed to provide an additional 10% damping to the Eurocode 8 compliant building. The structure was tested with and without dampers for two dierent levels of earthquake intensity. It was shown that the elastomeric dampers led to signicant decrease of displacements, accelerations, base shear forces, and permanent damage of the structure, even after ground motions scaled to the Maximum Considered Earthquake level. Lastly, Real Time Substructure tests were performed in order to further validate the proposed hysteretic model. Both SDOF and MDOF systems equipped with elastomeric dampers were tested under scaled version of the ElCentro ground motion and the corresponding force-displacement relationship of the dampers was compared with the analytical model. The results showed that the proposed model is able to capture the dynamic performance of the dampers under realistic earthquake conditions.